Intertemporal Prices and the U.S. Trade Balance - Burda, Michael C.; Gerlach, Stefan (American Economic Review, 1992)
The deterioration of the U.S. merchandise trade deficit in the 1980's fell mostly on durable goods. Using a representative-agent model, we show that the key distinction between the trade balance in nondurables and durables is the role of intertemporal prices in the latter. A decrease in intertemporal prices associated, for example, with an exchange-rate overvaluation should therefore be expected to worsen the trade balance in durables more than in nondurables. This interpretation of the compositional changes of the U.S. trade balance is supported by our econometric findings.